Chemotaxonomy Study and Antioxidant Activity of Five Phyllanthaceae Family Plants in West Java - Kusriani, Herni; Naki, Maulana Isman; Budiana, Wempi (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Phyllanthaceae is one of the medicinal plants family which it’s species widely spread in Indonesia with many chemical content and various pharmacological activities. Based on the previous research, it said that plants belonging to the same family will show the same chemical compound phenomenon. The purpose of this research was to determine the similarities of anatomical characteristics, chemical contents, total flavonoid content as the main compound, and antioxidant activity of five plants of the Phyllanthaceae family (the leaves of katuk, meniran, ceremai, buni, and mareme) in West Java. Five plants of the Phyllanthaceae family were observed macroscopically and identified their chemical compounds by phytochemical screening and thin layer chromatography. Each leaf was macerated using 96% ethanol as solvent and determined total flavonoid content and antioxidant activity. Determination of total flavonoid content with AlCl3 reagent with quercetin as a standard. Antioxidant activity assay conducted by the DPPH method (1,1-diphenyl-picrylhydrazil) with acid ascorbic as standard was measured at 515 nm. The results of macroscopic observations of five leaves of the Phyllanthaceae family showed some similarities in terms of morphology, including in compound leaf type, but there are differences in terms of size. And from monitoring the compounds showed a similar distribution of compounds with flavonoid compounds as markers on Rf 0,61. The total flavonoid content of katuk, meniran, ceremai, buni, and mareme leaf extracts respectively were 9.465±0.029; 9.847±0.029; 7.504±0.090; 7.857±0.103; 7.318±0.029 mgQE/g, and their antioxidant activity expressed in IC50 values respectively were 79.720±0.18; 60.871±0.15; 80.728±0.10; 80.447±0.18; 82.676±0.10 g/mL, and ascorbic acid was 7.91±0.01 g/mL. Five plants of the Phyllanthaceae family have similar anatomical characteristics and chemical constituents and showed high levels of flavonoids with strong antioxidant activity.